On the Design of Low-Cost 60-GHz Radios for multigigabit-per-second transmission over short distances. - Smulders, Peter (IEEE Communications magazine)
This article reviews, discusses, and proposes crucial 60-GHz radio design options. First, it discusses the choice of integrated circuit technology for the radio frequency (RF) part and presents the status quo concerning standardization. Then, it describes the 60-GHz channel-propagation characteristics and proposes antenna solutions, as well as the architecture of the RF part, including a channelization scheme and frequency synthesizer architecture. With regard to the baseband part, we discuss the use of multicarrier modulation and compare it to single-carrier modulation. Finally, we demonstrate the consequences of the various design options as judged from link-budget calculations.